2009
DOI: 10.1007/s11243-009-9203-2
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous water oxidation by bidentate Schiff base manganese complexes in the presence of cerium(IV) ammonium nitrate

Abstract: Oxygen evolution was observed upon mixing solid manganese(III) bidentate Schiff base complexes with aqueous solutions of cerium(IV) ammonium nitrate. However, oxygen evolution was not observed upon mixing solutions of the complexes (in acetonitrile) with Ce(IV). Electron-withdrawing substituents on the Schiff base ligands (NO 2 , Br) enhanced the reactivity of the manganese complexes toward oxygen evolution. Oxygen evolution was also affected by R groups on the ligands, in the order Me [ Et ) Bz.Electronic sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…We reported on Mn(II), MnO 4 À and insoluble Mn products which show weak absorption bands characteristic of an {Mn 2 O 2 } core in the region of 600e700 cm À1 [13]. Using ESI(þ)eMS/MS at pH~4.5 we also showed that the mononuclear complex [Mn(tptz)(CH 3 COO)(OH 2 ) 2 ]NO 3 is not fully preserved and is in equilibrium with some cationic species [15].…”
Section: Mn Oxides As True Catalysts For Water Oxidationmentioning
confidence: 85%
See 1 more Smart Citation
“…We reported on Mn(II), MnO 4 À and insoluble Mn products which show weak absorption bands characteristic of an {Mn 2 O 2 } core in the region of 600e700 cm À1 [13]. Using ESI(þ)eMS/MS at pH~4.5 we also showed that the mononuclear complex [Mn(tptz)(CH 3 COO)(OH 2 ) 2 ]NO 3 is not fully preserved and is in equilibrium with some cationic species [15].…”
Section: Mn Oxides As True Catalysts For Water Oxidationmentioning
confidence: 85%
“…Previously, we reported on an oxygen-evolution reaction upon mixing solid Mn(III) bidentate Schiff base complexes with aqueous solutions of Ce(IV) [13]. We reported on Mn(II), MnO 4 À and insoluble Mn products which show weak absorption bands characteristic of an {Mn 2 O 2 } core in the region of 600e700 cm À1 [13].…”
Section: Mn Oxides As True Catalysts For Water Oxidationmentioning
confidence: 98%
“…Oxygen evolution was also observed upon mixing solid manganese(III) bidentate Schiff base complexes with aqueous solutions of (NH 4 ) 2 [(Ce(NO 3 ) 6 ] (Najafpour & Boghaei, 2009). However, oxygen evolution was not observed upon mixing solutions of the complexes (in acetonitrile) with Ce(IV).…”
Section: Schiff Base Complexmentioning
confidence: 99%
“…Electron-withdrawing substituents on the Schiff base ligands (NO 2 , Br) enhanced the reactivity of the manganese complexes toward oxygen evolution. Oxygen evolution was also affected by R groups on the ligands, in the order Me>Et > Bz (Najafpour & Boghaei, 2009). (Fig.…”
Section: Schiff Base Complexmentioning
confidence: 99%
“…The cell was charged with Ce(IV). Cerium(IV) ammonium nitrate (0.01 M) was dissolved in 25 ml water magnetically stirred at 25.0 0 C. Ce(IV) was stable in this condition and oxygen evolution was not observed (Yagi and Narita 2004;Najafpour and Boghaei 2009). After deaeration of Ce(IV) with nitrogen, the compounds as solid suspensions were added and oxygen evolution was recorded with the oxygen meter under stirring (Scheme 2).…”
Section: Water Oxidation Experimentsmentioning
confidence: 99%